Ethnically targeted advertising : views of those not targeted - Ernest Cyril, de Run (Asia Pacific Journal of Marketing and Logistics, 2007)
This paper sets out to extend current knowledge on advertising effects on those not targeted by noting unintended consequences on attitudinal, emotional, and behavioral reactions.